Impact of Community Policing Training and Program Implementation on Police Personnel in Arizona, 1995-1998 - Haarr, Robin N. ([Verlag nicht ermittelbar], 2003)
This study examined the impact on police trainees of the Phoenix Regional Training Academy's curriculum. The academy's basic training program integrates community policing and problem-oriented policing across the curriculum. A multiple-treatment single-case design was used to study 446 police recruits from 14 successive academy classes that began basic training classes between December 1995 and October 1996. The Police Personnel Survey, adapted from Rosenbaum, Yeh, and Wilkinson (1994), Skogan (1994, 1995), and Wycoff and Skogan (1993), was administered to officers in the study on four separate occasions. This instrument was designed to take repeated measures of police officer attitudes and beliefs related to various dimensions of the job, including job satisfaction, community policing, problem-solving policing, traditional policing, the role of the police, relations with the community, and multicultural sensitivity.